1990
DOI: 10.1055/s-0038-1647148
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Lupus-Like Anticoagulants by an Enzyme-Linked Immunosorbent Assay Using a Partial Thromboplastin as Antigen; A Comparative Study

Abstract: SummaryClotting assays allow qualitative rather than quantitative detection of the lupus anticoagulant. We have therefore studied the usefulness of an ELISA using a commercial partial thromboplastin, Thrombofax, oS antigen; the results obtained on 146 selected patient plasmas were compared to the results of coagulation tests (kaolin clotting time, tissue thromboplastin inhibition test, activated partial thromboplastin time) and of ELISAs using cardiolipin or phosphatidylserine as antigen. While satisfactory ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…5,6 However, the so-called anticardiolipin antibodies (aCLs) also bind to other negatively charged PLs, such as phosphatidylserine. 7 Affinity purification of aCLs revealed that aCL binding to cardiolipin depends on a plasma protein, ␤ 2 -glycoprotein I (␤ 2 GPI). [8][9][10] It is now generally accepted that autoimmune aPLs are directed against proteins binding to anionic PL surfaces rather than against PLs themselves, the major protein targets appearing to be ␤ 2 GPI and prothrombin.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, the so-called anticardiolipin antibodies (aCLs) also bind to other negatively charged PLs, such as phosphatidylserine. 7 Affinity purification of aCLs revealed that aCL binding to cardiolipin depends on a plasma protein, ␤ 2 -glycoprotein I (␤ 2 GPI). [8][9][10] It is now generally accepted that autoimmune aPLs are directed against proteins binding to anionic PL surfaces rather than against PLs themselves, the major protein targets appearing to be ␤ 2 GPI and prothrombin.…”
Section: Introductionmentioning
confidence: 99%
“…Arnout went on to replace cardiolipin with a commercial partial thromboplastin reagent or phosphatidylserine in the ELISA, hoping that this would more closely parallel the lupus anticoagulant activity. However, only moderate agreement was found between clotting tests and the various ELISAs, indicating that ELISA techniques cannot entirely replace coagulation tests for the detection of a lupus anticoagulant [23].…”
Section: Anticardiolipin Antibodiesmentioning
confidence: 99%
“…Anticardiolipin antibodies were determined using an enzyme immunosorbent assay (ELISA) as described (1) with minor modifications (20). Patient plasma samples were diluted 1:100 in phosphate buffered saline (PBS) containing 10% fetal calf serum unless stated otherwise; column fractions were diluted 1:20.…”
Section: Aizticardiolipiiz Antibodj Immunoassajmentioning
confidence: 99%